MENINGKATKAN KEAMANAN DATA KEUANGAN ENGAN METODE AES DI STMIK KRISTEN NEUMANN INDONESIA - Mahdianta Pandia Pandia (UPPM, 2017)
At present, the data stored in the computer is no longer safe, therefore data must be secured. To ensure the security and integrity of a data, an encoding process is needed. Encryption is done when data will be sent. This process will convert an original data into confidential data that cannot be read. Meanwhile, the decryption process is carried out to return data that has been encoded into the original data, the original data will not be read by unauthorized parties. The AES method is used as the latest standard cryptographic algorithm. the previous algorithm is considered incapable of securing data, because the key length is small. The AES method is a cryptographic algorithm using the Rijndael algorithm that can encrypt and decrypt 256 bits of data blocks.